Substrate modulation induced dual modification of ZnIn2S4-based photoelectrode for enhanced photoelectrocatalytic degradation and reduced the toxicity of ranitidine - Jiajun An; Yanan Li; Jiaxin Li; Lei Wang; Jiajin Hao; Lujie Nie; Bo Gao; Xudong Wang; Jin Wang; Rui Miao; Miaolu He; Danxi Huang (Environmental Chemistry and Ecotoxicology, 2025)
Photoelectrocatalytic (PEC) technology offers an effective means of eliminating pharmaceutical pollutants from water. However, the current methods for high-performance photoelectrode preparation still focus on complex modifications or compounding of the catalysts, and investigations of electrode substrates are lacking. Herein, this work employed four low-cost methods to modify a graphite felt (GF) substrate, and a series of ZnIn2S4 (ZIS)-based composite photoanodes were prepared via a hydrothermal method. The substrate modulation not only enhanced the intrinsic performance of the electrode but also had a regulatory effect on the morphology and crystal structure of the ZIS. Among them, the ZIS loaded on the electrooxidized GF (GF-E/ZIS) demonstrated a significantly improved photoresponse and charge transport abilities, reaction active area, and carrier separation efficiency. The PEC removal efficiency of ranitidine (RAN) by dual-modified GF-E/ZIS reached 92.06 %, with a reaction rate 17 times greater than that of unmodified GF/ZIS. Subsequently, GF-E/ZIS exhibited a broad pH treatment range and robust cycling stability. The modified substrate enhanced electron transport and further formed a Schottky junction with ZIS at the interface, effectively suppressing the recombination of carriers. Moreover, the dimethylamine and nitro groups in RAN are prone to attack and decomposition by reactive species, effectively reducing the risk of N-nitrosodimethylamine formation. The improved growth conditions of the mung beans revealed that PEC degradation by GF-E/ZIS effectively reduced the toxicity risk of water, thereby benefiting the ecological and environmental health. This work provides novel insights for the preparation of cost-effective, high-performance photoelectrodes for safer wastewater treatment.